2022
DOI: 10.1097/gox.0000000000004174
|View full text |Cite
|
Sign up to set email alerts
|

Patient Expectations for Symptomatic Improvement before Cubital Tunnel Release

Abstract: Background: Patient expectations before cubital tunnel release (CuTR), a common procedure that leads to incomplete symptom resolution for many patients, are unclear. Study purposes included (1) describing preoperative patient expectations, and (2) identifying factors affecting expectations. Methods: Included patients underwent isolated unilateral CuTR between 2015 and 2021 at a single tertiary academic medical center. Expectations regarding the level of symptomatic improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 69 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…It is unclear why these trends are seen. However, studies have reported that there are differences in the severity of cubital tunnel syndrome at the time of presentation by insurance type [3] as well as differences in patient expectations of the outcome of cubital tunnel release by insurance type [16], and these findings may affect postoperative outcomes. It is unclear why patients with workers compensation insurance may be at higher risk of revision surgery.…”
Section: Factors Independently Associated With Revision Cubital Tunne...mentioning
confidence: 99%
“…It is unclear why these trends are seen. However, studies have reported that there are differences in the severity of cubital tunnel syndrome at the time of presentation by insurance type [3] as well as differences in patient expectations of the outcome of cubital tunnel release by insurance type [16], and these findings may affect postoperative outcomes. It is unclear why patients with workers compensation insurance may be at higher risk of revision surgery.…”
Section: Factors Independently Associated With Revision Cubital Tunne...mentioning
confidence: 99%